Characteristics of consumer segments based on perceptions of the impact of digitalisation - Garai-Fodor, Mónika; Vasa, László; Jäckel, Katalin (Decision Making: Applications in Management and Engineering, 2023)
The focus of our research was to examine consumer perceptions of attitudes towards digitalisation. The perception of digitalisation was also analysed from a generation-specific perspective, given that the difference in values between generations is reflected in the perception of consumer trends, including the trend towards digitalisation. The primary data presented in this study are the results of a quantitative data collection was carried out among Hungarian consumers using an arbitrary sampling procedure. A pre-tested, standardised online questionnaire survey was used, which resulted in 3,515 evaluable questionnaires. Descriptive statistics, bivariate and multivariate analyses were used to process the quantitative results and test the hypotheses. As a result of the study, we were able to characterise three significantly distinguishable target groups using a K-means clustering procedure: the group of "consumers sceptical about digitalisation", the segment of "Accepting consumers who feel the differentiating effects of digitalisation", and The ’positive digital consumer’. We have been able to demonstrate that the perception of digitalisation can be used as a segmentation criterion, and we can also statistically demonstrate that the segments according to the perception of digitalisation carry generation-specific elements. In our opinion the results may help to increase consumer acceptance of digitalisation processes and related technologies. A limitation of the research is that, the results are valid for the population under consideration, cannot be considered representative. We believe that characterising the individual segments can help to differentiate the education process according to the awareness and attitudes of each consumer.